ISPC Portfolio-Level Commentary on CRP-II Full Proposals 2017-2022 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
This Commentary was written to inform discussions between Centers/CRPs/CO, donors and the ISPC and IEA to be held from 15.00 to 19.00h (Central European Time) on Thursday 16 June 2016.